Outcomes of Patent Ductus Arteriosus Stenting to Retrain Regressed Left Ventricle in Transposition of Great Arteries with Intact Ventricular Septum - ., AzizUllah; Sadiq, Nadeem; Mahmood, Amjad; Farhan, Muhammad Asad; Ikram, Madeeha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the outcomes of Patent Ductus Arteriosus (PDA) stenting to retrain regressed Left Ventricle (LV) in Transposition of Great Arteries with Intact Ventricular Septum (TGA-IVS). Study Design: Quasi-experimental study Place and Duration of Study: Paediatric Cardiology Department, Armed Forces Institute of Cardiology & National Institute of Heart Diseases, Rawalpindi Pakistan from July-Dec 2023 Methodology: Thirty pediatric patients aged < 2 months who underwent PDA stenting with TGA-IVS having regressed LV were included using non probability consecutive sampling. Prior to PDA stenting, echocardiography was performed in all TGA-IVS patients to evaluate the effectiveness of LV retraining.The Mosteller formula was used to relate LV mass to body surface area. Echocardiographic LV assessment was repeated at 1st and 2nd week after PDA stenting. Post stenting angiogram was carried out to confirm optimum placement and adequate blood flow to branch pulmonary arteries. Results: Among 30 participants, 19(63.3%) patients were males and 11(36.7%) were females with composite median age of 10.00(6.50-32.50) days. LV retraining using PDA stenting was found to be successful in 27(90.0%) patients and unsuccessful in 3(10.0%) patients. Successful patients exhibited high LV mass index [Pre stenting vs. post stenting: 33.00(32.00-34.00) g/m2 vs. 63.00(61.00-65.00) g/m2; p=0.005] and improved LV geometry after PDA stenting. However, the unsuccessful patients did not show an appropriate response because of large interatrial communication. Conclusions: PDA stenting significantly improved both left ventricular mass index and LV geometry. Moreover, transcatheter ductal stenting was an effective and safe method to retrain the regressed LV in late presenters of TGA-IVS.